Leveraging AlphaFold for innovation and sustainable health research in Africa - Emmanuel Nji; Katharina C. Cramer; Nicolas V. Rüffin; Fatoumata G. Fofana; Walid Heiba; Safiétou Sankhe (Nature Communications)
Without addressing the lack of research infrastructure, funding, and supportive science policies, structural biology capacity-building efforts in Africa will continue to be hindered by the persistent challenge of brain drain.